Problems with Global Education: Conceptual Contradictions - Young, J. Melanie (Alberta Journal of Educational Research, 2010)
Global education is concerned with social justice and student empowerment. However, an understanding of the word global as merely international and/or intercultural may fail to challenge existing mechanistic and compartmentalized views of knowledge and curriculum. Such a global education limits students’ agency and reproduces the very systems it intends to challenge. A holistic understanding of the word global allows for a relational or systems view of the world, mindful of the complex, multiple, and dynamic nature of living systems. It situates the students and their studies in the world and thus offers greater possibilities for action.